THE MALAY KINGDOM AND THE SPREAD OF ISLAM IN JAMBI: A STUDY OF LOCAL HISTORY AND RELIGIOUS TRADITIONS - Adisty Ningtiyas; Nyayu Soraya; Baldi Anggara (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the Malay kingdom and the spread of Islam in Jambi in relation to local history and religious traditions. This study examines the role of the Jambi Malay Kingdom in the process of spreading Islam since the 15th century AD, with a focus on the transition from a Hindu-Buddhist kingdom to an Islamic sultanate through trade, political marriages such as that of Ahmad Salim (Datuk Paduka Berhala) with the daughter of Pagaruyung, and the preaching of ulama. The study explores the history of Islamization through heritage sites such as the Orang Kayo Hitam Site, the Olak Kemang Stone House, the Seribu Pilgrimage Mosque, and the Gentala Arasy Museum, which reflect the acculturation of Islam with local Malay culture. In addition, the religious traditions of the Jambi Malay community are discussed such as the commemoration of Assyura, Nisfu Sya'ban, grave pilgrimages, and the art of Zapin-hadrah which integrates Islamic law with local customs, demonstrating the harmony of religion and culture until now. This study uses a historical method (library research) consisting of four stages, namely heuristics, source criticism, interpretation, and historiography. The data collected comes from various sources, such as books, articles, and documents relevant to the topic discussed.